2022
DOI: 10.1001/jamapediatrics.2022.0515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Suicides Among US Adolescents During the COVID-19 Pandemic

Abstract: We thank Jodee McDaniel, MS, Ohio State University, for her support in editing and reformatting this manuscript during the submission process. She was not compensated for her contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 4 publications
(9 reference statements)
2
41
1
2
Order By: Relevance
“…1 , 47 studies were included in the systematic review (study characteristics are reported in Table 1 ). 32 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 Among these studies, 43 were included in the meta-analytical process, for a total of around 65 million subjects (suicides: 63,120,235; suicidal behaviors: 934,951; suicidal ideation: 156,234): two reporting rates of deaths for suicides, 48 , 50 26 reporting prevalence data about suicidal behaviors 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 <...…”
Section: Resultsmentioning
confidence: 99%
“…1 , 47 studies were included in the systematic review (study characteristics are reported in Table 1 ). 32 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 Among these studies, 43 were included in the meta-analytical process, for a total of around 65 million subjects (suicides: 63,120,235; suicidal behaviors: 934,951; suicidal ideation: 156,234): two reporting rates of deaths for suicides, 48 , 50 26 reporting prevalence data about suicidal behaviors 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 <...…”
Section: Resultsmentioning
confidence: 99%
“…For adolescent girls, emergency visits related to suicide were up by 50%. Yet, Charpignon et al’s [ 39 ] assessment of suicide counts from 14 state health departments describes the difference in suicide rates across states. Although most states reported increases in adolescent suicides, several states reported decreases in suicide during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to identity-based stigma, victimization, or discrimination puts LGBTQ+ students at greater risk than their cisgender and heterosexual peers of experiencing poor academic achievement and mental health problems [ 11 , 12 , 20 , 32 , 38 ]. Several pre-pandemic studies suggest suicide attempts among the general U.S. population has remained relatively unchanged in the last decade [ 39 , 40 , 41 ], although the rates among adolescents have increased according to the Centers for Disease Control [ 39 , 42 , 43 , 44 ]. Although suicide rates have been decreasing among LGB youth, Raifman et al [ 45 ] indicate that LGB youth remain 3 times more likely to attempt suicide.…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. has witnessed a pediatric mental health (MH) crisis, with up to 20% of children experiencing a diagnosable MH-condition, 1 and COVID-19 exacerbating a perfect storm as stressors to youth have markedly increased during the current pandemic, 2,3 exposing deficiencies in our pediatric MH-care system. Schools play a critical role as the most common point of entry for accessing MH-services to children.…”
Section: Introductionmentioning
confidence: 99%